Possible mitochondrial dysfunction in a patient with deafness, dystonia, and cerebral hypomyelination (DDCH) due to BCAP31 Mutation. Issue 3 (17th January 2020) - Shimizu, Kenji; Oba, Daiju; Nambu, Ryusuke; Tanaka, Manabu; Oguma, Eiji; Murayama, Kei; Ohtake, Akira; Yoshiura, Koh‐ichiro; Ohashi, Hirofumi
Abstract: Background: Deafness, dystonia, and cerebral hypomyelination (DDCH) is an X‐linked disorder due to hemizygous mutations of BCAP31 . Methods: We report an 8‐year‐old boy with DDCH who possibly accompanied mitochondrial dysfunction. Clinical evaluation, respiratory chain enzyme assay, and whole exome sequencing analysis were performed. Results: Mitochondrial dysfunction was suspected by respiratory chain enzyme assay on his cultured skin fibroblasts which showed significantly decreased complex I enzyme activity. Whole exome sequencing analysis revealed a recurrent BCAP31 mutation (c.97C>T:p.Gln33*) which confirmed the diagnosis of DDCH for the patient. Conclusion: We speculate that mitochondrial dysfunction may be a feature in patients with DDCH. Abstract : Deafness, dystonia, and cerebral hypomyelination (DDCH) is an X‐linked disorder due to hemizygous mutations of BCAP31 . Mitochondrial dysfunction may be associated with DDCH.